One in, one out: Generic circumscription within subtribe Manilkarinae (Sapotaceae). Issue 1 (31st December 2022) - Randriarisoa, Aina; Naciri, Yamama; Armstrong, Kate; Boluda, Carlos Galan; Dafreville, Stephanie; Pouchon, Charles; Gautier, Laurent
Abstract: Previous phylogenetic studies have demonstrated that the Manilkarinae are a monophyletic subtribe if Northia is excluded. The subtribe consists of four genera: Faucherea, Labourdonnaisia, Labramia and Manilkara . However, the same phylogenetic studies also raised taxonomic issues concerning unclear generic delimitations and unresolved relationships. The current study's aims are: to resolve these taxonomic issues using a molecular phylogeny based on hundreds of nuclear markers sequenced from a representative sampling of taxa across the four genera; to find relevant morphological characters allowing the distinction of the clades retrieved with the phylogeny; and finally to understand the evolutionary history of the subtribe by conducting a divergence time estimation and ancestral state reconstructions. Our phylogeny shows a well‐resolved backbone with four main lineages: the Labramia clade, the main clade of Manilkara, a clade in which all species of Labourdonnaisia and Faucherea are mixed, and a clade of three Pacific Manilkara species. The main clade of Manilkara is retrieved as sister to Labramia, and the Labourdonnaisia ‐ Faucherea clade is clearly assessed as sister to the three Pacific Manilkara species. As a consequence, Faucherea is synonymized with Labourdonnaisia, and the three Pacific Manilkara are considered to be a separate genus, for which the name Abebaia is resurrected. We provide emended descriptions for Labourdonnaisia and Abebaia as well as the necessary new combinations. The ancestral state reconstruction of flower characters shows that ancestral Manilkarinae were characterized by a hexamerous corolla, well‐developed dorsal appendages and staminodes, and a pubescent ovary. These character states have been retained in the main Manilkara clade, but surprisingly also in Abebaia, which appears as a cryptic genus. The lack of dorsal appendages and the reduction of staminodes observed in Labourdonnaisia appeared after the split from Abebaia . The increase in corolla merism observed mainly in the Mascarene Labourdonnaisia, which was used to separate it from Faucherea, appears to be a derived state, which evolved separately in a few species during the radiation of Labourdonnaisia on Madagascar and the Mascarenes. The glabrous ovary state observed in Labramia also constitutes a derived synapomorphic state in the genus.